Quantum Dots and Their Use in Solar Cells (Al-Farooq Journal of Sciences, 2026)
Quantum dots (QDs) have gained significant attention as advanced light-absorbing materials in photovoltaic systems due to their tunable bandgaps, high absorption coefficients, and potential for multiple exction generation(MEG). These nanoscale semiconductors offer a pathway to surpass the efficiency limits of traditional solar cells through spectral tuning and enhanced photon-to-electron conversion mechanisms. This paper reviews the funda- mental properties of QDs relevant to solar energy conversion, including quantum confinement behavior, charge carrier dynamics, and synthesis approaches. It also explores recent advances in QD-based solar cell architec- tures—such as sensitized, heterojunction, and tandem configurations—highlighting performance metrics, inte- gration challenges, and environmental considerations. Finally, it outlines future directions in QD photovoltaics, including the use of non-toxic materials, scalable fabrication methods, and AI-assisted material discovery. These insights emphasize the transformative potential of QDs in advancing low-cost, high-efficiency solar technologies.
Keywords: Quantum Dots, Solar Cells, Multiple Exciton Generation, Nanocrystals, Photovoltaics, and Energy Conversion